European butterfly populations vary in sensitivity to weather across their geographical ranges. Issue 12 (20th October 2017) - Mills, Simon C.; Oliver, Tom H.; Bradbury, Richard B.; Gregory, Richard D.; Brereton, Tom; Kühn, Elisabeth; Kuussaari, Mikko; Musche, Martin; Roy, David B.; Schmucki, Reto; Stefanescu, Constantí; van Swaay, Chris; et al.
Abstract: Aim: The aim was to assess the sensitivity of butterfly population dynamics to variation in weather conditions across their geographical ranges, relative to sensitivity to density dependence, and determine whether sensitivity is greater towards latitudinal range margins. Location: Europe. Time period: 1980–2014. Major taxa studied: Butterflies. Methods: We use long‐term (35 years) butterfly monitoring data from > 900 sites, ranging from Finland to Spain, grouping sites into 2° latitudinal bands. For 12 univoltine butterfly species with sufficient data from at least four bands, we construct population growth rate models that include density dependence, temperature and precipitation during distinct life‐cycle periods, defined to accommodate regional variation in phenology. We use partial R 2 values as indicators of butterfly population dynamics' sensitivity to weather and density dependence, and assess how these vary with latitudinal position within a species' distribution. Results: Population growth rates appear uniformly sensitive to density dependence across species' geographical distributions, and sensitivity to density dependence is typically greater than sensitivity to weather. Sensitivity to weather is greatest towards range edges, with symmetry in northern and southern parts of the range. This pattern is not driven by variation in the magnitude of weather variability across the range, topographic heterogeneity, latitudinal range extent or phylogeny. Significant weather variables in population growth rate models appear evenly distributed across the life cycle and across temperature and precipitation, with substantial intraspecific variation across the geographical ranges in the associations between population dynamics and specific weather variables. Main conclusions: Range‐edge populations appear more sensitive to changes in weather than those nearer the centre of species' distributions, but density dependence does not exhibit this pattern. Precipitation is as important as temperature in driving butterfly population dynamics. Intraspecific variation in the form and strength of sensitivity to weather suggests that there may be important geographical variation in populations' responses to climate change.